Robust deep semi-supervised learning with label propagation and differential privacy - Yan, Zhicong; Li, Shenghong; Duan, Zhongli; Zhao, Yuanyuan (Frontiers in Computer Science, 2023)
Semi-supervised Learning (SSL) methods provide a powerful tool for utilizing abundant unlabeled data to strengthen standard supervised learning. Traditional graph-based SSL methods prevail in classical SSL problems for their intuitional implementation and effective performance. However, they encounter troubles when applying to image classification followed by modern deep learning, since the diffusion algorithms face the curse of dimensionality. In this work, we propose a simple and efficient SSL method, combining graph-based SSL paradigm with differential privacy. We aim at developing coherent latent feature space of deep neural networks so that the diffusion algorithm in the latent space can give more precise predictions for unlabelled data. Our approach achieves state-of-the-art performance on the Cifar-10, Cifar-100 and Mini-imagenet benchmark datasets, and obtains an error rate of 18.56% on Cifar-10 using only 1% of all labels. Furthermore, our approach inherits the benefits of graph-based SSL methods with a simple training process and can be easily combined with any network architecture.